Setting Eyes on the Retinal Pigment Epithelium - Moreno-Marmol, Tania; Cavodeassi, Florencia; Bovolenta, Paola (Frontiers in Cell and Developmental Biology, 2018)
The neural component of the zebrafish eye derives from a small group of cells known as the eye/retinal field. These cells, positioned in the anterior neural plate, rearrange extensively and generate the optic vesicles. Each vesicle subsequently folds over itself to form the double-layered optic cup, from which the mature eye derives. During this transition, cells of the optic vesicle are progressively specified towards three different fates: the retinal pigment epithelium (RPE), the neural retina, and the optic stalk. Recent studies have shown that folding of the zebrafish optic vesicle into a cup is in part driven by basal constriction of the cells of the future neural retina. During folding however, RPE cells undergo an even more dramatic shape conversion that seems to entail the acquisition of unique properties. How these changes occur and whether they contribute to optic cup formation is still poorly understood. Here we will review present knowledge on RPE morphogenesis and discuss potential mechanisms that may explain such transformation using examples taken from embryonic Drosophila tissues that undergo similar shape changes. We will also put forward a hypothesis for optic cup folding that considers an active contribution from the RPE.